SISTEM INFORMASI PEMBAYARAN KOMITE SEKOLAH BERBASIS WEB - Anastasia Mude; Ba’diah Puang Arsyad (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
The School Board is an independent body designed to accommodate the environmental or community role in schools. At SMA Negeri 1 Ende, the role of the school committee is to monitor and control student contributions to the school. The management of committee funds is handled directly by the school committee's finance department, and the recording process is still recorded in the general ledger so errors often occur. As a result, the treasurer has difficulty making income accountability reports and student reports that have not been or have been paid. The purpose of this research is to create a committee payment management system that will make the process of managing committee payment information faster, easier and more efficient. The software developed uses the Waterfall SDLC (Software Development Life Cycle) model, the programming languages ??used are PHP and CSS, and database management uses MySQL. System design uses an object-oriented approach and UML (Unified Modeling Language) modeling. The results of functional testing using black box testing. The results obtained from this study are the implementation of a committee payment information system, which will facilitate payment transactions and management of committee payment data by the committee treasurer.